Encoding and Navigating Linguistic Representations in Memory - Matthew Wagers (Frontiers Research Topics, 2017)
Successful speaking and understanding requires mechanisms for reliably encoding structured linguistic representations in memory and for effectively accessing information in those representations later. Studying the time-course of real-time linguistic dependency formation provides a valuable tool for uncovering the cognitive and neural basis of these mechanisms. This volume draws together multiple perspectives on encoding and navigating structured linguistic representations, to highlight important empirical insights, and to identify key priorities for new research in this area.